"I Can Write in My Language and Switch Back and Forth?": Elementary Teacher Candidates Experiencing and Enacting Translanguaging Pedagogies in a Literacy Methods Course. (November 2020) - Machado, Emily; Gonzales, Grace Cornell
Although existing research examines how pre-K–12 teachers understand everyday translanguaging and enact translanguaging pedagogies in their literacy classrooms, considerably less research explores translanguaging pedagogies in literacy teacher education. Drawing on García, Johnson, and Seltzer's theorization of translanguaging stance, design, and shifts, we redesigned a university-based literacy methods course to encourage both English-medium and dual-language teacher candidates (TCs) to engage their full linguistic repertoires in writing. In this study, we used qualitative methods to explore how TCs in our course experienced translanguaging pedagogies in coursework and enacted them with students in fieldwork settings. Findings illustrate that TCs experimented with language within our university classroom, drawing on their full linguistic repertoires in course assignments and countering the dominance of English in course activities. They also showcase how TCs began enacting translanguaging pedagogies in their fieldwork placements, planning intentionally for translanguaging in lesson plans, and tapping into the translanguaging corriente in everyday teaching and learning. Ultimately, this study offers insights into the potential of enacting translanguaging pedagogies in preservice literacy teacher education for English-medium and dual-language educators alike.